2020
DOI: 10.1016/j.surfcoat.2020.125393
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric behaviour of Bi-Te films on polymer substrates DC-sputtered at room-temperature in moving web deposition

Abstract: High-throughput roll-to-roll processing could be used to scale up the manufacture of flexible thermoelectric generators. Very thin thermoelectric layers can be manufactured at high throughput speed and low cost and, most importantly, are predicted to possess better thermoelectric properties than thicker layers. Here we present a study on a series of bismuth telluride films of different thickness (few nm to 370 nm), deposited on polymer substrates at room temperature using DC magnetron sputtering. Unlike previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…The authors. Tao et al and Morgan et al demonstrated considerable progress in other publications to optimize chalcogenide-based devices on the lab scale [5][6][7]14]. Significant research and development are still required for industrialization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors. Tao et al and Morgan et al demonstrated considerable progress in other publications to optimize chalcogenide-based devices on the lab scale [5][6][7]14]. Significant research and development are still required for industrialization.…”
Section: Resultsmentioning
confidence: 99%
“…Webs of flexible substrates are wound at high speeds, e.g., 10-500 m min −1 from one roll, through processing chambers, back onto another roll. Multiple layers of a device can be deposited in sequential deposition steps within a single pass of the R2R [4][5][6][7][8]. Physical vapour deposition (PVD) techniques, such as sputtering and thermal evaporation, offer high-quality and tuneable thin films and recently demonstrated promising R2R compatibility for high-throughput manufacturing of f-TEGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Among them, only sputtering shows the most promise for scale-up manufacture of TEGs like R2R processing. [29] Hence, sputtering is employed in this study.Flexible thin-film TEGs can be assembled in both crossplane (CP-TEG) and in-plane (IP-TEG) structural designs, which allow heat flows/TE legs perpendicular and parallel, respectively, to the substrate. [30] CP-TEG has already been commercialized in bulk TEGs and some μTEGs, however, to further decrease the size to nanorange, the crossplane configuration is not practical since maintaining a large ΔT across a nanothick TE leg is an almost impossible challenge [14,31] and the power output is very poor (e.g., refs.…”
mentioning
confidence: 99%
“…[28] Among them, only sputtering shows the most promise for scale-up manufacture of TEGs like R2R processing. [29] Hence, sputtering is employed in this study.…”
mentioning
confidence: 99%